Comportamento do teste ML Flow em pacientes e contatos de pacientes com hansenías e menores de 18 anos - Maria Aparecida Alves Ferreira (2007)
This descriptive and exploratory study had the objective of evaluating ML Flow, one of the serologic tests developed to aid leprosy control. Data on 115 newly diagnosed leprosy patients and 1,011 household contacts, all under 18, were analyzed to determine seropositivity ratios and factors associated to a positive test result. Statistical analysis included logistic regression and classification tree method. The ML Flow test result was positive in 21.7% of the patients and 19.7% of the contacts. In the group of patients, logistic regression analysis indicated association of seropositivity with positive skin smear (OR = 18) and number of skin lesions higher than five (OR = 5.86). Seropositivity probability for a patient with a positive skin smear and more than five skin lesions was 0.94. According to classification tree analysis, seropositivity was shown to be associated with the following variables: skin smear, Madrid classification, number of nerves involved and age. In the group of contacts, index patient classification, age and type of health service were associated to seropositivity in both analyses. Contacts of multibacillary (MB) index patients had a chance of seropositivity two times higher (OR = 2.31) than those of paucibacillary (PB) index patients. For each additional year of age, the chance of seropositivity for the contacts was 1.06 times higher (OR = 1.06). Seventeen year old contacts of MB index patients, attended in health units had the highest probability of seropositivity (0.37). The variables which best explained seropositivity in the population studied were those associated to higher bacillary loads. Therefore, the ML Flow test could also be used in childhood to aid the correct classification of patients for treatment and to identify those contacts who have an increased risk of developing leprosy, leading to a timely diagnosis. These actions could impact leprosy transmission and incidence in all ages.